Knowledge-based system for categorization and selection of creativity support techniques in design - Botega, Luiz Fernando de Carvalho (2016)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2016.